Peran Kepemimpinan Visioner Dalam Optimalisasi Skill Di Lembaga Pendidikan Vokasi: Studi Kasus Di Akademi Komunitas Darussalam - Hamid, Abdul; M Taufiqurohman; M Alam Surya N (CV. Kalimasada Group, 2025)
This study aims to examine the role of visionary leadership in optimizing skills in vocational education institutions, with a case study focusing on the Darussalam Community Academy. The main focus of this study is how a leader with a long-term vision is able to design a skills development strategy that is in line with industry needs and job market dynamics. The method used in this study is a qualitative approach with a case study technique, involving in-depth interviews with institutional leaders, lecturers, and students, as well as field observations of the learning and skills training process. The results of the study indicate that visionary leadership contributes significantly to climate transformation, increased collaboration with industry partners, and the creation of an adaptive and future-oriented learning ecosystem. Visionary leaders are not only drivers of innovation, but also catalysts in building a productive and collaborative work culture in the academic environment. This study makes an important contribution to the literature on vocational education leadership by emphasizing that a strong and strategic leadership vision can be the key to improving the quality of vocational graduates who are competent, relevant, and ready to compete in the world of work.